The taxonomy and nomenclature of Kalanchoe ser. Rotundifoliae, a cluster of small-growing to medium-sized species with narrowly urceolate flowers here included in K. sect. Kalanchoe (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae), with the description of a new series, K. ser. Hirtae - Smith, Gideon F. (Phytotaxa, 2026)
As the circumscription of Kalanchoe ser. Rotundifoliae (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae) is refined here this cluster of species includes glabrous, small-statured plants with small, erect, narrow-tube, abruptly urn-shaped, chromatic flowers that are different shades of red and orange, but never white. The flowers show distinct diurnal movement, and the corolla tubes and corolla lobes become tightly twisted post-anthesis. In outline, the succulent leaves of the species included in K. ser. Rotundifoliae are variable, but often cylindrical, round, or obovate. To accommodate, also at the rank of series, a related cluster of glabrous or tomentose species with a flower morphology that varies from abruptly urn-shaped to more angular-cylindrical, with leaves that are often weakly succulent, round to obovate and flat, and with yellow or orange flowers that usually display weak diurnal movement or none at all, K. ser. Hirtae is described as new. With some exclusions, these two groups, i.e., K. ser. Rotundifoliae and K. ser. Hirtae, of predominantly southern African kalanchoes are placed in K. sect. Kalanchoe in K. subg. Kalanchoe. Kalanchoe ser. Rotundifoliae was previously included in K. sect. Raveta but is therefore here transferred to K. sect. Kalanchoe. The species included in K. ser. Rotundifoliae and K. ser. Hirtae, respectively, are enumerated and a selection from both series is illustrated. Those southern African kalanchoes with overall similar gross vegetative and reproductive morphologies that are excluded from these two series are listed.